110 Effects of Dietary Phytoestrogens on Aneurysm Wall Inflammation and Intracranial Aneurysm Formation. (1st April 2022) - Baranoski, Jacob F.; Rutledge, Caleb; Yokosuka, Kimihiko; Kamio, Yoshinobu; Kuwabara, Atsushi; Sato, Hiroki; Rahmani, Redi; Purcell, James; Eguchi, Satoru; Margaryan, Tigran; Tovmasyan, Artak; Ai, Jinglu; et al.
Abstract : INTRODUCTION: The discovery of pharmacologic treatments that can reduce the incidence of aneurysm formation or rupture is of considerable interest. Prior studies demonstrated that supplemental estrogen can protect against the formation and rupture of aneurysms in ovariectomized female mice. This is of particular clinical significance, as post-menopausal women are at an increased risk for aneurysmal rupture. However, systemic estrogen hormone replacement is associated with adverse clinical outcomes primarily due to off-target effects thus limiting its clinical applicability. Isoflavones are plant-based, diet-derived compounds that structurally resemble estrogens but exhibit tissue and receptor specificity resulting in the potential for targeted, tissue-specific activation of estrogen receptors while limiting potentially deleterious off-target effects. METHODS: Using a systemic hypertension and elastase injection murine model, we induced intracranial aneurysms in ovariectomized adult female mice. We fed the mice with an isoflavone-free diet with/without daidzein supplementation or in a combination of intraperitoneal equol; a separate group were also given oral vancomycin. Experiments were repeated using estrogen-receptor-beta knockout mice. RESULTS: Both dietary daidzein and supplementation with its metabolite, equol, were protective against aneurysm formation in ovariectomized mice. The protective effects of daidzein and equol required estrogen-receptor-beta. Oral vancomycin induced disruption of the intestinal microbial conversion of daidzein to equol abolished the protective effects of daidzein against aneurysm formation. mRNA expression analyses demonstrated that mice treated with equol had lower inflammatory cytokines in the cerebral arteries, suggesting that phytoestrogens modulate inflammatory processes important to intracranial aneurysm pathogenesis. CONCLUSION: Our study establishes that both dietary daidzein and its metabolite - equol - are protective against aneurysm formation in ovariectomized female mice through the activation of estrogen-receptor-beta and subsequent suppression of inflammation. Dietary daidzein's protective effect required the intestinal conversion to equol. Our results indicate the potential therapeutic value of dietary daidzein and equol for the prevention of the formation of intracranial aneurysms and related subarachnoid hemorrhage.